SYNCRETIC UNITY OF SOCIAL AND TRADITIONAL RESPONSIBILITY IN TRADITIONAL CULTURE - Matyukhina, Oleksandra (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The peculiarities of understanding the ethical category of "responsibility" in traditional culture from the philosophical and cultural standpoints are studied. Its all-encompassing nature and syncretic unity of social and environmental responsibility are emphasized. The aim and tasks are the relations of the norms of social and environmental responsibility in traditional culture. Therefore, the heritage of traditional culture in this direction acquires special significance in a new round of historical development. Research methods. To implement this task, a cultural-historical methodological approach and analytical and descriptive methods areused. Research results. The author notes that traditional society provided a high level of social responsibility. Social responsibility was extended to nature. Its compliance was ensured by strict adherence to time-tested norms and rules turned intotraditions. Social and environmental responsibility act as a syncretic whole in traditional culture. Folk traditions preserve it and fix it in the individual and social consciousness. It is emphasized that the study and use of traditional cultural heritage is a necessary condition for the establishment of responsibility as a basic value of modern society, which provides the concept of sustainable development. Discussion. In the late XX and early XXIcenturies, the problem of environmental responsibility attracts much attention from philosophers, sociologists, culturologists, and other humanities. It is noted that the decisive role in the implementation of the problems of environmental responsibility in the scientific community was played primarily by the works of A. Schweizer, K. Mayer-Abiha, the concepts of G. Jonas, E. Levinas, E. Fromm. An important stage in the study of traditional cultural heritage in the field of ecology is the formation and development of ethnic ecology. Conclusion. The experience of theinteraction of man andsociety with nature, accumulated in the traditions of culture is able to help find solutions to the environmental problems of today.